2003
DOI: 10.1007/s00259-003-1172-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of gallium-67 scan in defining the extent of disease in an endemic deep mycosis, paracoccidioidomycosis: a predominantly multifocal disease

Abstract: The tools currently used to evaluate the extent of paracoccidioidomycosis (PCM) may be of limited value in detecting subclinical lesions. The aim of this study was to verify the role of gallium-67 whole-body scan in evaluating the extent of disease of 65 patients with active PCM. The (67)Ga scan findings were compared with the results of clinical evaluation, chest radiography and/or high-resolution computed tomography (CT), abdominal ultrasound (US) or CT, laryngoscopy, CT or magnetic resonance imaging (MRI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Such involvement has been minor when the cortisol delta was determined after ACTH administration (14%) or when basal cortisol has been taken as a tool to diagnose adrenal failure 1,2 . Additionally, tomographic, ecographic and nuclear medicine images have revealed subclinical involvement of these glands 5,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Such involvement has been minor when the cortisol delta was determined after ACTH administration (14%) or when basal cortisol has been taken as a tool to diagnose adrenal failure 1,2 . Additionally, tomographic, ecographic and nuclear medicine images have revealed subclinical involvement of these glands 5,14 .…”
Section: Discussionmentioning
confidence: 99%
“…These become enlarged, producing lymph node hypertrophy, hepatomegaly, and splenomegaly. Usually, there is no clinically apparent lung involvement, but image studies have revealed pulmonary abnormalities in all cases (55,103). As its names implies, it is a disease of the young and is diagnosed mainly in undernourished children and adults less than 30 years of age.…”
Section: The Acute/subacute (Juvenile) Formmentioning
confidence: 99%
“…Older classifications subdivided this form into unifocal and multifocal, referring to lesions being present in one or in various organs (43,46). Image and scan studies have revealed that the mycosis is a multiorgan disease regardless of the presence or absence of symptoms related to a particular organ (55,75,103).…”
Section: The Chronic Adult Formmentioning
confidence: 99%
See 1 more Smart Citation
“…These become hypertrophic, generating, lymph node enlargement and hepatosplenomegaly. Usually, there is no clinically apparent pulmonary involvement, but imaging studies have revealed pulmonary abnormalities in all cases [17] [18].…”
Section: Introductionmentioning
confidence: 99%